ANALISISIS KEMAMPUAN LITERASI SOSIAL SISWA DALAM PEMBELAJARAN IPAS KELAS III SDN 137 PALEMBANG - Rizal Ardiansyah Rizal; Murjainah; Hermansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze students' social literacy skills in the Science and Social Studies (IPAS) subject in Grade III at SDN 137 Palembang. Social literacy is a crucial aspect of character development that includes four main indicators: self-awareness, emotional understanding and regulation, understanding of social situations, and relationship-building. This research uses a descriptive qualitative approach with data collected through observation, interviews, documentation, and tests. The results show that students demonstrate a fairly good ability to understand themselves and regulate their emotions, especially in real-life social situations such as helping peers or working collaboratively. Their understanding of social situations and ability to form relationships are also developing, although challenges remain in responding to more complex and implicit social problems, such as peer pressure or hidden social conflicts. The highest achievement was found in indicators related to empathy and cooperation, while lower performance appeared in analyzing social issues and showing moral courage. Therefore, IPAS learning is expected to be developed further in contextual and reflective ways to enhance students' overall social awareness. These findings emphasize the importance of integrating social values into early education so that students grow not only cognitively but also socially and emotionally.